Perspectives from the 2nd International Post-Tuberculosis Symposium: mobilising advocacy and research for improved outcomes - B.W. Allwood; R. Nightingale; G. Agbota; S. Auld; G.P. Bisson; A. Byrne; R. Dunn; D. Evans; G. Hoddinott; G. Günther; Z. Islam; J.C. Johnston; et al. (IJTLD Open)
In 2020, it was estimated that there were 155 million survivors of TB alive, all at risk of possible post TB disability. The 2nd International Post-Tuberculosis Symposium (Stellenbosch, South Africa) was held to increase global awareness and empower TB-affected communities to play an active role in driving the agenda. We aimed to update knowledge on post-TB life and illness, identify research priorities, build research collaborations and highlight the need to embed lung health outcomes in clinical TB trials and programmatic TB care services. The symposium was a multidisciplinary meeting that included clinicians, researchers, TB survivors, funders and policy makers. Ten academic working groups set their own goals and covered the following thematic areas: 1) patient engagement and perspectives; 2) epidemiology and modelling; 3) pathogenesis of post-TB sequelae; 4) post-TB lung disease; 5) cardiovascular and pulmonary vascular complications; 6) neuromuscular & skeletal complications; 7) paediatric complications; 8) economic-social and psychological (ESP) consequences; 9) prevention, treatment and management; 10) advocacy, policy and stakeholder engagement. The working groups provided important updates for their respective fields, highlighted research priorities, and made progress towards the standardisation and alignment of post-TB outcomes and definitions.